PERAN MANAJER TERHADAP KINERJA KEUANGAN PADA BANK RAKYAT INDONESIA TBK - Siti Rohani; Yulfiswandi Yulfiswandi; Herman Eka Putra; Herliyanti Sanjaya (Journal of Global Business and Management Review, 2022)
The research we conducted to analyze the role of managers in improving financial performance at PT. Bank Rakyat Indonesia Tbk. in 2017 to 2021. The population in this study is PT. Bank Rakyat Indonesia Tbk. The research method used is documents and literature. To measure financial performance here, researchers use ratio calculations, namely ROA (Return On Assets), ROE (Return On Equity), NIM (Net Interest Margin), BOPO. To find out the ROA (Return On Assets) ratio, net profit after tax and income is required. As for calculating the ROE (Return On Equity) net profit ratio needed after interest and taxes and capital. And for NIM (Net Interest Margin) the ratio requires total net profit after tax and income, while BOPO (Operating Expenses against Operating Income) requires operational and operating income. The results showed that the percentage ratio ROA (Return On Assets) 1.16% -2.50%, ROE (Return On Equity) 8.13% -17.5%, NIM (Net Interest Margin) 9.31% -11 .47%, BOPO (Operating Expenses to Operating Income) 52.66% - 72.13%.